PENERAPAN MODEL PEMBELAJARAN NUMBERED HEAD TOGETHER (NHT) BERBANTUAN MEDIA AUDIO VISUAL UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS VIII SMPN3 NUNUKANSELATAN - Siska Siska; Vlorensius Vlorensius; Zulfadli Zulfadli (Program Studi Pendidikan Biologi Universitas Borneo Tarakan, 2020)
A teacher must be able to create conducive atmosphere of learning, innovative and creative by sticking to a student-oriented approach. This can be realized through various ways, one of them is learning by applying various suitable learning models and supporting learning media. This study aimed to improve science achievement of the VIII grade students at SMPN 3 Nunukan Selatan by applying the Numbered Head Together (NHT) learning model assisted by audio-visual media. This was a Classroom Action Research which consisted of two cycles. Each cycle consisted of two meetings followed by stages of planning, action,observation and reflection. The instruments used in this study were observation sheets of teacher activities and student activities, assessment sheets (aspects of attitude and skills), test results and student worksheets (aspects of knowledge). The results showed that the NHT assisted by audio-visual media improved science achievement of the VIII grade students at SMPN 3 Nunukan Selatan. Classically, there was an increase in the learner achievement from the first cycle to the second cycle in all three aspects measured. For the aspect of knowledge there was an increase from 50% in the first cycle to 79% in the second cycle. For the aspect of attitude there was an increase from 64% in the first cycle to 96% in the second cycle. For the aspect of skills there was an increase from 61% in the first cycle 86% in the second cycle. Thestudents’ scores reached the completeness indicator (75%). In addition, the observations result of teacher teaching activities in the first cycle was 82 (very good category) and the second cycle was 86(very good category).The observation result of student activities in the first cycle was 70% (good category) and in the second cycle was 93% (very good category).Keywords: Numbered Head Together, Audio Visual Media, Learning Outcome